DIVERSIFIKASI MATA PENCARAIAN PERTANI KERAMBA JARING APUNG (KJA) AKIBAT PENCEMARAN SUNGAI OGAN (Studi Kasus Kecamatan Indralaya, Kabupaten Ogan Ilir (OI), Sumatera Selatan) - Yusmiono, Boby Agus (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA, 2018)
Ogan river was polluted when dry and rainy season. The farmers of Keramba Jaring Apung needed big modal and got big profit. However the farmers of Keramba Jaring Apung also had big loss. This research was cultural research which was done by taking object on farmers of Keramba Jaring Apung of Muara Penimbung Ilir village, Indralaya sub-district, Ogan Ilir district, South Sumatera. The researcher had limited the problem so that the problem was not wide. (1). The researcher explained the impact of river pollution for the farmers of Keramba Jaring Apung. (2) . This research did not discuss the details of the physical condition of river pollution because it required laboratory research. This research used case study description and qualitative research methods, the purpose of that method was to see all of activities from the farmers of Keramba Jaring Apung. Techniques of collecting data used interviews, observation, and documentation. From the result of field research conducted, the researcher saw the society of Muara Penimbung Ilir was still trauma with the modal which borrowed fron the bank, so that they returned the debt of their business. The society of Muara Penimbung Ilir diversified to replace their livelihood such as: traders, framers, farming, songket and making cakes or culinary foods. Nevertheless there were also still defended to be farmers  of keramba jaring apung with big modal was ready to lose or loss due to river pollution. Keywords— Livelihood diversification, Farmers of Keramba Jaring Apung